Reducing microbial contamination risk and improving physical properties of plant-based mayonnaise produced using chickpea aquafaba - Muhialdin, Belal J.; Mohammed, Nameer Khairullah; Cheok, H. J.; Farouk, Abd ElAziem; Meor Hussin, Anis Shobirin (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2021)
Aquafaba is obtained by soaking different types of legumes and utilised in the production of several plant-based foods due to its functional properties. The present work aimed to evaluate the effects of aquafaba produced by soaking chickpeas at different durations on the safety, physicochemical properties, and consumer acceptability of plant-based mayonnaise. The chickpea aquafaba was prepared by soaking chickpea at different durations of 12, 18, and 24 h, and later boiled for 35 min at 120°C. The results demonstrated significantly (p < 0.05) higher TSS (5.89 ± 0.00), viscosity (7.23 ± 0.06), and peptide content (0.463 ± 0.001) in chickpea aquafaba soaked for 24 h. The mayonnaise prepared with 24 h chickpea aquafaba showed improved firmness (129.47 ± 9.64 g) and consistency (860.26 ± 26.52 g/s). The bacterial load was observed to decrease in 24 h chickpea aquafaba mayonnaise (3.857 ± 0.948 log CFU/g), and increased by one-fold in 12 h chickpea aquafaba mayonnaise (4.672 ± 0.588 log CFU/g) after 35 days at 28 ± 2°C. The consumer acceptability evaluation showed no significant difference (p > 0.05) among all the tested attributes with the 24 h aquafaba mayonnaise received the highest score for taste (6.80 ± 1.38). The aquafaba produced from chickpeas soaked for 24 h and boiled for 35 min has high potential for applications in plant-based mayonnaise production to enhance safety and improve physicochemical and consumer acceptability.